Using a portable monitoring device for diagnosing obstructive sleep apnea in patients with multiple coexisting medical illnesses. (8th August 2021) - To, Kin Wang; Chan, Tat On; Chan, Wing Chi; Choo, Kah Lin; Hui, David S. C.
Abstract: Introduction: The existing guidelines recommend type III devices should be used in patients without significant comorbidities. Objectives: This study explored the reliability of using a type III device in patients with significant medical conditions to diagnose sleep apnea. Methods: Patients had an overnight sleep study conducted simultaneously with both polysomnography (PSG) and a type III (NOX‐T3) monitoring device. All patients had stable multiple coexisting medical illnesses without any changes in medications and conditions within 1 month of sleep study. Results: Between July 2019 and March 2020, there were altogether 74 patients recruited with analyzable data. Five major disease groups were identified in the cohort: psychiatric illnesses, stroke, ischemic heart diseases (IHDs), chronic kidney diseases (CKDs), and others. Psychiatric patients with medications were found to have the lowest apnea hypopnea index (AHI) (23.7 per hour) and arousal index (46.6 per hour). The CKD group had the highest mean arousal index (71.4 per hour) and obstructive apnea count (110.2). NOX‐T3 respiratory event index (REI) was significantly lower than the PSG AHI (mean REI 31.4 vs. mean AHI: 42.2). The number of patients with no/mild/moderate/severe obstructive sleep apnea (OSA) diagnosed by NOX‐T3 and PSG was 7/17/19/31 and 5/11/20/38, respectively. Conclusion: NOX‐T3 device can reliably diagnose OSA in patients with different stable coexisting medical conditions. There is a tendency for underestimation of the severity of the OSA with NOX‐T3 in patients with coexisting medical conditions especially with sedative medications. A positive NOX‐T3 reliably diagnoses OSA whereas a negative NOX‐T3 result needs to be interpreted with caution.